EFFECTS OF ANIONS AND CATIONS OF IONIC LIQUIDS ON CLAY SWELLING: EXPERIMENTAL AND SIMULATION APPROACHES - RAHMAN, MD TAUHIDUR (2021)
Ionic liquids (ILs) can play a vital role in preventing clay swelling during hydraulic fracturing. Research have indicated that the length of the side chain attached to the cationic core has an effect on the inhibitor’s performance. However, the cations and polyatomic anions may also have the ability to inhibit clay swelling. In this study, five ILs were utilized to assess the effects of cations and polyatomic anions on clay swelling inhibition. The ILs’ performances were compared with a commonly used inhibitor, potassium chloride. X-ray diffraction test was used to check the mineral composition of a bentonite clay sample utilized in this research. The ability of these ILs to suppress clay swelling and their rheological properties were determined using linear swelling and rheological tests. The swelling inhibition mechanisms were studied using zeta potential, Fourier-transform infrared spectroscopy, and contact angle measurements. Moreover, COSMO-RS computer simulation was conducted to further explain the inhibition mechanisms.